Comparing the Ecotoxicological Effects of Perfluorooctanoic Acid (PFOA) and Perfluorohexanoic Acid (PFHxA) on Freshwater Microbial Community - Laine, Miikka B.; Vesamäki, Jussi S.; Puupponen, Veli-Mikko; Tiirola, Marja; Taipale, Sami J. (Frontiers in Environmental Science, 2022)
The ubiquitous presence of perfluorinated carboxylic acids (PFCAs) around the globe has attracted increasing attention, due to their persistency, bioaccumulation, and toxicity. As these concerning factors are highly related to the length of the carbon backbone of the compound, the production and use of long-chain PFCAs has been restricted by regulations. Consequently, manufacturers have replaced the long-chain PFCAs with short-chain PFCAs. However, the increasing amount of data on the environmental behavior, toxicity, and possible detrimental human and environmental effects associated with the use of short-chain PFCAs, has caused long-term safety concerns. Simultaneously, the ecotoxicological effects of the compounds on aquatic microorganisms has remained understudied. Hence, the present study focused on determining, and comparing, the effects of regulated long-chain PFCA, perfluorooctanoic acid (PFOA), and nonregulated short-chain PFCA, perfluorohexanoic acid (PFHxA), on the diversity, structure, microbial growth, and activity of a freshwater microbial community. In the experiment, lake water was incubated for a period of four weeks at three different concentrations of the studied PFCAs: 100 ng/l, 100 µg/l, and 10 mg/l. The results suggested that both compounds at high concentration (10 mg/l) altered the structure of the microbial community, but the diversity was not affected. Both compounds also decreased the microbial biovolume at higher concentrations and the increasing dose added to the significance of the impact, whereas inhibition of net microbial respiration could not be demonstrated. PFOA showed more potent toxicity towards the microbial community as it caused more significant structural changes to the community and significantly inhibited microbial growth even at the low 100 ng/l concentration. This study helps to better understand the ecotoxicity of PFCAs and to assess the environmental risks associated with their use. Additionally, these results can help policy makers to better assess the environmental risks posed by short-chain PFCAs on aquatic ecosystems.